2021
DOI: 10.30534/ijatcse/2021/861032021
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evidence of Socially-Engineered Attack Menace Among Undergraduate Smartphone Users in Selected Universities in Nigeria

Abstract: Smartphone proliferation today, have up-scaled user adoption of Internet-based processing activities. These include (not limited to) e-learning, e-commerce, mobile-banking and others –all aimed at better performance, service delivery at improved execution speed, greater portability, flexibility and accessibility ease. Thus, necessitating growth expansion in mobile-app development across varying platforms that are poised to help users accomplish processing tasks while harn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Phishing is an identity theft targeted at compromising sensitive unsuspecting victim's data often for personal gains [18]. Phishing can involve the creation of compromised websites, the acquisition of email lists and botnets, and spoofing of mails, SMS designed to deceive an unsuspecting victim into downloading the malicious contents therein as originating from a legitimate and trustworthy source(s) [5], [8]. A phishing attack has three (3) elements: a lure, hook and catch.…”
Section: Phishing Susceptibility: a Review Of Related Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Phishing is an identity theft targeted at compromising sensitive unsuspecting victim's data often for personal gains [18]. Phishing can involve the creation of compromised websites, the acquisition of email lists and botnets, and spoofing of mails, SMS designed to deceive an unsuspecting victim into downloading the malicious contents therein as originating from a legitimate and trustworthy source(s) [5], [8]. A phishing attack has three (3) elements: a lure, hook and catch.…”
Section: Phishing Susceptibility: a Review Of Related Literaturementioning
confidence: 99%
“…It has been observed that another feature that influences susceptibility to phish attacks is gender, age as well as online presence pattern. Users between the ages of 18 and 29 were identified as being the most susceptible to phishing attacks on both email and social media platforms [8], [39]; while females between the Int J Elec & Comp Eng ISSN: 2088-8708  ages of 24 to 42 were identified as being the most vulnerable to phishing attacks. This can be attributed to the fact that these young adults and females are constantly engaged to boycott social seclusion-leading to addiction [40].…”
Section: Demographicsmentioning
confidence: 99%
See 2 more Smart Citations